An antenatal alcohol service evaluation of the north-east of England and north Cumbria. (18th February 2020) - Howlett, Helen
Abstract: Background: NHS England's 'Better Births' strategy aims to improve maternal and infant health outcomes. A strategic priority identified in the north-east local maternity system is to reduce alcohol consumption in pregnancy due to the documented diverse risks of harm to mother and baby, including foetal alcohol spectrum disorder. Aims: To evaluate current alcohol prevention, screening and treatment service provision in maternity care across the region, and inform future recommendations. Methods: A service evaluation survey was developed to systematically consult strategic stakeholders across all nine maternity trusts in the region over a 2-month period in 2018. Content analysis was employed to identify fundamental themes and inform recommendations for practice. Results: High variation was reported throughout regional clinical practices, service provision and staff training. For example, a number of alcohol screening tools were identified, each with diverse thresholds for referral; reported data collection and documentation practices were multifarious, incomparable and unquantifiable; audit was rare and guidelines were primarily influenced by local commissioning agreements. Discussion: Standardized patient pathways involving alcohol screening and management practices are required, and sharing best practices will facilitate referrals and support regardless of location. The implementation of these recommendations requires appropriate leadership, commissioning and training strategies.